Glycomyces amatae sp. nov., isolated from a yellow-ringed grass moth (Amata sperbius). Issue 11 (9th November 2022) - Suriyachadkun, Chanwit; Ngaemthao, Wipaporn; Pujchakarn, Tawanmol; Chamroensaksri, Nitcha; Niemhom, Nantawan; Chunhametha, Suwanee
Abstract : A novel mycelium-forming actinomycete strain, designated A-F 0318 T, was isolated from a yellow-ringed grass moth ( Amata sperbius ) collected from Phitsanulok Province, Thailand. Long chains of non-motile cylindrical spores with a smooth surface developed on aerial mycelia. The polyphasic taxonomic study suggested that strain A-F 0318 T belonged to the genus Glycomyces . The 16S rRNA gene sequence analysis indicated that strain A-F 0318 T was closely related to Glycomyces harbinensis LL-DO5139 T with 97.94 % sequence similarity. The average nucleotide identity (ANI) based on blast, ANI based on the MUMmer algorithm and average amino acid identity values of strain A-F 0318 T with G. harbinensis LL-DO5139 T were 86.9, 89.1 and 84.24 %, respectively. The digital DNA–DNA hybridization value between A-F 0318 T and its closest relative, G. harbinensis LL-DO5139 T was 33.8 %. The digital G+C content of the genomic DNA was 71.7 mol%. The cell-wall peptidoglycan contained meso -diaminopimelic acid. The whole-cell sugars contained ribose, xylose, glucose and galactose. The predominant menaquinone was MK-10(H4 ). The predominant fatty acids were iso-C16 : 0, anteiso-C15 : 0, anteiso-C17 : 0 and iso-C16 : 1 G. The polar lipid profile consisted of diphosphatidylglycerol, phosphatidylglycerol, phosphatidylinositol, phosphatidylinositol mannoside, two unknown phosphoglycolipids and one unknown phospholipid. Based on comparative analysis of genotypic, phenotypic and chemotaxonomic data, the novel actinomycete strain A-F 0318 T (=TBRC 13612 T =NBRC 115417 T ) represents the type strain of a novel species, for which the name Glycomyces amatae sp. nov. is proposed.